MANIC DEPRESSIVE DISORDER OF THE MAIN CHARACTER AS SEEN IN Mr. JONES MOVIE (PSYCHOLOGYCAL APPROACH) - Mao, Regina; Separ, Fransiskus M; Kara, Yuliana M D K (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
This study aimed at finding out the symptoms and the treatment of manic depressive disorder as seen in “Mr. Jones” movie. This study using Hodges theory to analysis the symptoms and treatment of manic depressive disorder. The method that used in this study were descriptive qualitative. The data in this study were taken from quotations such as word,phrases,dialogue and sentences. The result shows that there are fifty five utterances contain three symptoms and treatment of the manic depressive or bipolar disorder. These data are categorized as mania which data seen thirty nine data its contain of extreme elevated mood or euphoria is an excessive feeling of joy are four data, grandiosity are six data seen, irritability are nine data, rapid speech are four data, racing thought are six data, impulsiveness are three data, risk sexual behaviors is one data and excessive spending are six data. The hypomania symptoms are five data contain of desire and drive for success contain of hopeless are five data, and uncontrollable swings of racing thoughts which coincide with feelings of despair and blackness one data. While the treatment of manic depressive disorder are exercise to increase confident and positive image is one data, medications are three data, therapy to increase mental health and physical health are two data.